National food security through corporate globalization: Japanese strategies in the global grain trade since the 2007–8 food crisis. Issue 5 (28th July 2020) - Hall, Derek
ABSTRACT: English-language research on the contemporary global grain trade says little about Japan. Japanese firms, however, have made extensive overseas investments in grain production and trading since 2007, becoming major players in the soya trade between North and South America and China, and the Japanese state has developed policies promoting 'foreign agricultural investment' in grains. This paper documents and explains these developments by exploring the legacies of earlier Japanese grain trade moves, examining three visions of the relationship between foreign agricultural investment and Japan's food security, and arguing that conceptualizations of Japan as an 'Asian land grabber' fit awkwardly with the empirical record.